По эту сторону фронта : [роман] / Владислав Конюшевский - Конюшевский Владислав Николаевич (Ленинградское издательство, 2011)
Экземпляры: ф.15 (20150216) / Инвентарный номер: 46443 / Цена: 100.00 / Авт.знак: К 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6